Determinants of Gen Z Work Productivity in Retail and E-Commerce: The Role of Perceived Ease of Technology, FoMO, and Emotional Spending - Desi Ratnasari; Suhardi; Mat Amin; Rahmad Firdaus (JURNAL ECONOMINA, 2026)
This study aims to examine the determinants of work productivity among Generation Z employees in the retail and e-commerce sector by analyzing the roles of perceived ease of technology, Fear of Missing Out (FoMO), and emotional spending. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from 200 Generation Z employees working in retail and e-commerce industries in Indonesia through a structured questionnaire using a five-point Likert scale. The measurement model was evaluated using validity and reliability tests, while the structural model was assessed through path coefficients, R-square, and predictive relevance. The results reveal that perceived ease of technology has a positive and significant effect on work productivity, indicating that user-friendly systems enhance efficiency and performance. In contrast, FoMO and materialism do not show significant effects on productivity, suggesting that psychological factors may not directly influence work outcomes in this context. Furthermore, emotional spending does not significantly affect productivity and does not mediate the relationship between the independent variables and work productivity. These findings highlight that technological factors are more dominant than psychological and behavioral factors in shaping productivity among Generation Z employees in digital work environments, particularly in retail and e-commerce sectors.